Reinterpreting Khilafah through Prophetic Islam: From Theocratic Legacy to Democratic Ethics - Mukotip; Aziz Muslim (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2025)
The discourse on khilafah and democracy is often viewed as two contradictory poles, a perspective that tends to be reductive since both are interpreted merely as political systems. This research aims to clarify the true essence of khilafah and to examine possibilities of reconciling it with democratic principles. The issue is significant because it contributes to the theoretical debate in Islamic political thought and has practical relevance for Muslim societies that struggle between religious ideals and democratic governance. The study employs two approaches: thematic interpretation to uncover the Qur’anic meaning of khilafah, and Kuntowijoyo’s Prophetic Social Science to integrate its ethical dimensions with democracy. The findings show that khilafah is not a state system, but a divine character emphasizing imitation of God and personal responsibility. It also manifests as a movement based on knowledge rather than mere belief. The study concludes that khilafah and democracy are not inherently contradictory. Future discourse is advised to focus on developing the ethical and scientific dimensions of khilafah to enrich democratic practices within Muslim societies.